PERANCANGAN PLASTIC WASTE SHREDDER MACHINE PORTABLE DI KAMPUS POLMAN BANDUNG - Ariefijanto, Dedy; Novianty, Nadhifah Rysca; Komara, Asep Indra (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
Plastic Waste Shredder Machine is a machine that is used to reduce the size of waste into small pieces for recycling process. This machine is a development from previous machines. The design methodology in this study is VDI 2222. Determination of component dimensions is based on analysis of critical components with the help of Computer Aided Engineering software. This machine works by inserting plastic bottle waste to the hopper, the size will be reduced in shredding area with two-blade system that moves oppositely with a fixed knife on each side, and the result is the plastic chips with a maximum size of 5x5 mm. After the design process, the machine is operated with an electric motor with a power of 0,75 kW and output rotation of 50 rpm. This machine can process 10 kg/day plastic waste with machine dimensions of 400 x 600 x 900 mm and total machine weight of 124 kg.